NAFTA: MORE THAN A REGIONAL TRADE AGREEMENT - Uner, Firat; Assoc. Prof. Dr.M. Cem OĞULTÜRK (International Journal of Business and Social Science Research, 2024)
Trade is one of the fundamental reasons underlying the relationships between societies. Commercial interactions have contributed to the establishment of a specific international system worldwide through the trade relations between empires and states. In the 20th century, interstate trade led to the formation of certain agreements, some of which gave rise to regional-scale trade alliances. The North American Free Trade Agreement (NAFTA) is one of the regional trade agreements documented among North American countries, holding significant importance not only in increasing trade volume among signatory nations but also in terms of fostering regional cooperation and closer political relations. Despite being criticized by many since its signing date, NAFTA underwent substantial changes in 2020 and was restructured under the name The United States-Mexico-Canada Agreement (USMCA). Despite controversies and criticisms, NAFTA played a significant role in strengthening regional economic, social, and political ties, becoming one of the prominent examples of the rising regional trade agreements worldwide after the 1990s. In this study, the motivation behind NAFTA's inception, its historical development, member countries, and the positive impacts on the region are discussed. The contributions of NAFTA to the North American economy and regional development are examined through the analysis of gathered data, reports, and academic studies. The study aims to discuss the findings on the impact of NAFTA not only as a trade agreement but also on regional social and political developments.